a UPAYA PENCAPAIAN KESEJAHTERAAN PSIKOLOGIS (PSYCHOLOGICAL WELLBEING) MELALUI PERSPEKTIF TEKNIK DESAIN ARSITEKTUR RUANG: UPAYA PENCAPAIAN KESEJAHTERAAN PSIKOLOGIS (PSYCHOLOGICAL WELLBEING) MELALUI PERSPEKTIF TEKNIK DESAIN ARSITEKTUR RUANG - zulham, hanif; Diva, Firda Rahma (JURNAL PERSPEKTIF ARSITEKTUR, 2025)
Psychological well-being is a condition in which individuals are able to attain inner peace, life satisfaction, and adaptive stress management. The physical environment, particularly architectural space, plays a significant role in shaping human psychological experiences through visual, auditory, and spatial stimuli. This study aims to examine the role of architectural spatial design techniques in supporting the achievement of psychological well-being from an environmental psychology perspective. This research adopt a qualitative descriptive approach using a systematic literature review method. Data sources were obtained from scientific journals, academic books, and relevant publications discussing the relationship between spatial design elements and psychological well-being. The analysis was conducted through concept identification, thematic categorization of findings, and synthesis between architectural design elements and theoretical frameworks of psychological well-being. The findings indicate that design elements such as natural lighting, color, ventilation, spatial layout, natural elements, and the healing environment concept contribute significantly to the fulfillment of psychological well-being dimensions, including environmental mastery, emotional stability, social connectedness, and life satisfaction. Thoughtfully designed architectural spaces function not only in an aesthetic and functional capacity but also as supportive environments for mental health and overall quality of life. These findings emphasize the importance of integrating psychological considerations into architectural spatial design processes.